Body shape concerns and behavioral intentions on eating disorders: a cross-sectional study of Chinese female university students using an extended theory of reasoned action model - Zhao, Jingyi; Zhao, Jing; Yuan, Han; Gao, Zeng (Frontiers in Nutrition, 2024)
BackgroundWeight and body shape concerns have become increasingly common among adolescents. Chinese university students show a high risk of eating disorder behaviors. This study aims to analyze the moderating effect of BMI on the relationships between body shape, attitudes, subjective norms, and eating disorder behavioral intentions among Chinese female university students using the Theory of Reasoned Action (TRA) model.MethodsA stratified random sample of 679 female Chinese university students (age, mean ± SD = 19.792 ± 1.007) participated in the study. The surveys comprised the Theory of Reasoned Action Questionnaire (TRA-Q) and the Body Shape Questionnaire (BS-Q) to assess their body shape concerns and behavioral intentions regarding eating disorders. Structural equation modeling was used to test the extended TRA model, with body shape as an additional predictor and BMI as a moderator.ResultsBody shape positively affected attitudes (β = 0.444, p < 0.001), subjective norms (β = 0.506, p < 0.001), and intentions (β = 0.374, p < 0.001). BMI significantly moderated the relationships between attitudes (t = −3.012, p < 0.01), subjective norms (t = −2.678, p < 0.01), and body shapes (t = −4.485, p < 0.001) toward eating disorder intentions.ConclusionBody shape and BMI directly influence eating disorder behavioral intentions among Chinese female university students. The findings suggest that young Chinese women’s eating disorder intentions are increasingly influenced by external factors related to body shape and BMI.